PERAN STRATEGIS PARTISIPASI MASYARAKAT DALAM MEMPERKUAT TRANSPARANSI DAN AKUNTABILITAS PENGELOLAAN KEUANGAN DESA BERDASARKAN PRINSIP GOOD GOVERNANCE - Nicodemus Rahabeat (ADISAM PUBLISHER, 2026)
This study aims to analyze the strategic role of community participation in strengthening transparency and accountability in village financial management based on the principles of good governance. Effective and accountable village financial management is one of the main indicators of successful village governance. The significant allocation of Village Funds requires transparent, accountable, and participatory governance to minimize potential irregularities and enhance public trust. This research employs a quantitative approach using descriptive and verificative methods. Data were collected through questionnaires distributed to respondents consisting of village officials, members of the Village Consultative Body (BPD), community leaders, and villagers involved in village deliberation meetings. The data analysis techniques include validity and reliability tests, descriptive analysis, and multiple linear regression analysis using statistical software. The results indicate that community participation has a positive and significant effect on the transparency of village financial management. Furthermore, community participation also has a positive and significant effect on accountability in village financial management. These findings imply that the higher the level of community involvement in planning, implementation, and supervision processes, the better the level of information disclosure and accountability demonstrated by the village government. Therefore, community participation plays a strategic role as one of the key pillars in implementing good governance principles at the village level. This study is expected to contribute to the development of public sector accounting literature and serve as a reference for village governments in improving transparent and accountable financial governance.